Association of Hypoalbuminemia with Risk of Death in Pediatric Patients with End Stage Renal Disease undergoing Hemodialysis: A Tertiary Care Experience in Pakistan - Shahida Perveen, Imran Ahmad, Muhammad Atif Anjum, Saad Qayyum, Ameen Ullah, Naureen Akhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most important and common feature of chronic kidney disease is Hypoalbuminemia and is considered a poor prognostic factor. Low levels of Serum albumin are a predictor of growth failure and are strongly associated with increase death rate in pediatric patients undergoing hemodialysis with End Stage Renal Disease (ESRD), especially a challenge in underdeveloped countries. Aim: To evaluate the association of serum albumin level with hospitalization and rate of death in ESRD hemodialyzed pediatric patients. Study Design: Cohort study Place and Duration of Study: Department of Pediatric Nephrology, University of Child Health Sciences, Lahore from 1st January 2018 to 31st January 2022 Methodology: Ninety two children on hemodialysis and aged 5-16 years were included. Data including patient demographics, anthropometry, date of dialysis initiation, diagnosis, systolic and diastolic blood pressure, dialysis access (HD line/AV fistula), laboratory parameters, compliance to dialysis prescription, and frequency of hospitalization and combined duration of hospital stay was recorded. Results: The mean age at dialysis was 10.6±2.7 years with male to female ratio of 1.3:1. The mean duration on dialysis was 2.03±0.9 years. In our study, CAKUT (42.4%) was the most commonly occurring underlying etiology of end stage renal disease, followed by cystic renal disease (27.2%) and glomerular disease (15.2%) respectively. Regarding the systolic hypertension 22.9% were hypertensive and 35.8% were pre-hypertensive (BP 90th to 95th percentile). For diastolic hypertension, 18.5% were hypertensive and 42.4%were noted as pre-hypertensive. Majority of patients (87%) had hypoalbuminemia (serum albumin < 3.5 gm/dl) at dialysis initiation. In our study the value of serum albumin has inverse relationship with \risk of mortality in ESRD hemodialyzed patients even after adjustment to other factors. There is a 70% higher risk of death with each 1gm/dl decline in serum albumin value (hazard ratio=0.300(0.122-0.740) P<0.009). In addition, AVF access group has a significantly lower risk of death compared to the catheter group (hazard ratio=0.444 (0.246-0.801), P = 0.007). On generation of ROC curves, AUC obtained for serum albumin was statistically significant (AUC=0.838, 95% CI 0.758–0.918). In our study, no correlation was found between hypoalbuminemia and annual frequency of hospitalization (P<0.812) and total duration of stay (P<0.997).For mortality prediction, our study demonstrated a cut off value of albumin of 3g/dl with sensitivity of 80% and specificity of 68.7%. Conclusion: The independent prognostic value of serum albumin in mortality prediction at a cut off value of 3g/dl. In the final model even after adjustment of other covariates, hypoalbuminemia at dialysis initiation and type of vascular access continued to be vital indicator of risk of death in pediatric ESRD patients. However, no statistically significant association was observed between hypoalbuminemia and hospitalization in dialysis patients. Keywords: ESRD, Hypoalbuminemia, Growth failure, Haemodialysis